Implementação e otimização de uma arquitetura de reverberação digital empregando técnicas de processamento multitaxa sobre plataforma reconfigurável - Sehn, Leandro Roberto (2009)
The following work presents a optimization proposal for a digital reverberation architecture applying multirate processing techniques over a reconfigurable platform. Reverberation is one of the acoustic effects that most occur in our lives. Although very common, this phenomenon is often imperceptible. It is noteworthy that the presence of reverberation has a paramount importance, particularly in the musical environment, since it adds sense of space to the recordings (or executions) of a particular song, making it sounds more natural. Due to this importance, the first artificial reverbs came much time before digital computers. These simulators were electro-acoustic devices that simulated the reverberation making use of springs or steel plates equipped with transducers. With the appearance of the first digital computers, digital signal processing techniques began to be used, leading to the first digital reverbs that simulate the reverberation using linear filters in discrete time. Considering the recent developments experienced in the configurable computing field, there is a natural tendency to research and develop acoustic systems based on such a platform. The multirate signal processing is characterized by changing the signal sampling frequency from the removal or addition of samples in the original input sequence. Depending on the application, changing the frequency of sampling can greatly reduce the algorithms and hardware complexity. As the reverb effect is based on digital delay lines which size is proportional to the sampling frequency, and, since multirate processing techniques allow the frequency reduction, is possible visualise the reduction in memory needed to implement the effect in question. In this sense, the architecture of digital reverb proposed by James A. Moorer was chosen as the basis for development and comparison. From the results of this work, it is highlighted the reduction in memory consumption by 50% compared to the reference architecture. Regarding the results compatibility, the proposed architecture presented a satisfactory response, being imperceptible the differences between the reference architecture and the proposed one. At last, it is emphasized that the proposed architecture can be used to build other audio effects based on time delays, which will benefit from the reduction in memory consumption afforded by the proposal. This considerable reduction in memory enables the proposed architecture utilization on a single low-cost chip and presents a new way to manage computational resources required by digital reverberators.